ASSISTING INTERIOR DESIGN CLASS USING ONLINE 3D APPLICATION - Alkhalidi, Abdulsamad; Izani, Mohammed (PEOPLE: International Journal of Social Sciences, 2017)
Learning visual subject that involves creativity, technicality and drawing skills is very challenging, time consuming and sometimes very frustrating. It requires passion and patience in order to understand and master the skills. Our study focuses on implementing a method to assist the students in understanding visual subject particularly perspective drawing in interior architecture program at the College of Fine Arts and Design (CFAD), University of Sharjah. An online 3D application known as Autodesk Homestyler has been used to assist sophomore students to understand perspective drawings. The main problems for these students are difficulties in visualizing and understanding 3D space, scale, proportion and object depth in perspective drawing. Implementation of this method allows the students to understand the subject effectively. Samples of student work, before and after the implementation are shown to demonstrate the effectiveness of this method. The result shows that traditional drawing skills that enhanced and aided by the technology such as online 3D application will give more result that is promising and this hybrid method has great potential for future development.